Clinical and radiographic outcome of a treat-to-target strategy using methotrexate and intra-articular glucocorticoids with or without adalimumab induction: a 2-year investigator-initiated, double-blinded, randomised, controlled trial (OPERA). Issue 9 (21st October 2015) - Hørslev-Petersen, K; Hetland, M L; Ørnbjerg, L M; Junker, P; Pødenphant, J; Ellingsen, T; Ahlquist, P; Lindegaard, H; Linauskas, A; Schlemmer, A; Dam, M Y; Hansen, I; et al.
Abstract : Objectives: To study clinical and radiographic outcomes after withdrawing 1 year's adalimumab induction therapy for early rheumatoid arthritis (eRA) added to a methotrexate and intra-articular triamcinolone hexacetonide treat-to-target strategy (NCT00660647 ). Methods: Disease-modifying antirheumatic drug (DMARD)-naive patients with eRA started methotrexate (20 mg/week) and intra-articular triamcinolone (20 mg/ml) for 2 years. In addition, they were randomised to receive placebo adalimumab (DMARD group, n=91) or adalimumab (40 mg/every other week) (DMARD+adalimumab group, n=89) during the first year. Sulfasalazine and hydroxychloroquine were added if disease activity persisted after 3 months. During year 2, synthetic DMARDs continued. Adalimumab was (re)initiated if active disease reoccurred. Clinical response, remission, disability, quality of life and radiographic changes were assessed. Results: One year after adalimumab withdrawal, treatment profiles and clinical responses did not differ between groups. In the DMARD/DMARD+adalimumab groups, the median 2-year methotrexate dose was 20/20 mg/week (p=0.45), triple DMARD therapy had been initiated in 33/27 patients (p=0.49), adalimumab was (re)initiated in 12/12 patients and cumulative triamcinolone dose was 160/120 mg (p=0.15). The treatment target (disease activity score, 4 variables, C-reactive protein (DAS28CRP) ≤3.2 or DAS28>3.2 without swollen joints) was achieved at all visits in ≥85% of patients in year 2; remission rates were DAS28CRP<2.6:69%/66%; Clinical Disease Activity Index ≤2.8:55%/57%; Simplified Disease Activity Index <3.3:54%/49%; American College of Rheumatology/European League against Rheumatism (28 joints):44%/45% (p=0.66–1.00). Radiographic progression (Δtotal Sharp score/year) was similar 1.31/0.53 (p=0.12). Erosive progression (Δerosion score (ES)/year) was year 1:0.57/0.06 (p=0.02); year 2:0.38/0.05 (p=0.005). Proportion of patients without erosive progression (ΔES≤0) was year 1: 59%/76% (p=0.03); year 2:64%/79% (p=0.04). Conclusions: An aggressive triamcinolone and synthetic DMARD treat-to-target strategy in eRA provided excellent 2-year clinical and radiographic disease control independent of adalimumab induction therapy. ES progression was slightly less during and following adalimumab induction therapy. Trial registration number: NCT00660647.